Optimalisasi Pemanfaatan Platform Merdeka Mengajar dalam Proses Belajar Mengajar PAI di SMPN 1 Lekok Pasuruan - Nurbayah, Siti; Munir, Miftakhul (Universitas Yudharta Pasuruan, 2025)
Digital transformation in education has become essential in the Merdeka Belajar era, including Islamic Religious Education (PAI). The Merdeka Mengajar Platform (PMM) serves as digital innovation supporting teacher professional development and facilitating interactive, meaningful learning. However, implementation remains suboptimal, particularly in schools with limited resources and digital competence. Objectives: 1) examine PMM optimization implementation in PAI learning at SMPN 1 Lekok Pasuruan; 2) identify supporting and inhibiting factors in optimization. Method: Qualitative case study with PAI teachers as subjects and informants including school principal, curriculum vice principal, non-PAI teachers, students, and student affairs vice principal. Data collected through observation, in-depth interviews, and documentation. Validity ensured through source and method triangulation; descriptive analysis employed. Results: 1) PMM optimization conducted through four strategic stages: initial condition analysis, platform utilization planning, implementation with training and mentoring, and periodic evaluation through teacher reflection and discussion. PAI teachers actively access PMM features including inspirational videos, teaching modules, and diagnostic assessments. 2) Supporting factors: teacher adaptability, strong leadership support, and basic digital facilities. Inhibiting factors: limited devices, unstable internet connectivity, and need for improved teacher ICT competence